The effect of time of day on anaerobic performance and blood lactate response in trained men: assessment in relation to chronotype - Köse, Yakup; Ulaş, Mehmet; Atay, Emrah; Yaşar, Hilal Ertürk (Frontiers in Physiology, 2025)
This study examined the effects of the time of day on anaerobic performance and blood lactate levels in 20 trained male athletes with intermediate type (IT) and close to evening type (CET) chronotypes. The athletes completed vertical jump and repeated sprint ability (6 × 20 m) tests at three different times (07:00-08:00 h, 13:00-14:00 h, and 18:00-19:00 h). Blood lactate levels were measured at baseline, post-RSA (3 min), and post-RSA (33 min). Results showed that peak power [F (2,36) = 18.437, p = 0.001, η2p = 0.506] and average power [F (2,36) = 25.677, p = 0.001, η2p = 0.588] for vertical jumps -hands on hips- [F (2,36) = 15.683, p = 0.001, η2p = 0.466] and hands-free [F (2, 36) = 11.200, p = 0.001, η2p = 0.427] and repeated sprint ability (6 × 20 mt) tests were significantly higher in the evening and afternoon compared to the morning, consistent with previous findings on circadian effects on neuromuscular function. Additionally, regardless of chronotype, significantly higher lactate accumulation was reported in the afternoon and evening hours compared to the morning hours at peak lactate levels at 3 min post-RSA [F (2,38) = 16.62, p = 0.001, η2p = 0.474]. Regarding recovery (33rd m) lactate levels, CET individuals showed significantly better lactate clearance in the evening compared to the morning and afternoon hours [F (2,36) = 7.125, p = 0.002, η2p = 0.284]. In contrast, IT individuals did not show time-dependent differences in recovery. These findings highlight the role of circadian rhythms in anaerobic performance and metabolic responses. Differences in lactate accumulation and clearance suggest that time of day and chronotype should be considered when designing training and recovery strategies.